THE ANALYSIS OF DEIXIS IN STUDENTS’ TALK IN LEARNING ENGLISH SPEAKING - Silvi Nurvagian; Rina Herlina (Universitas Galuh, 2021)
This research reports the types and the dominant types of deixis found in students’ talk in learning English speaking. The design of this study used a descriptive qualitative. The present study was carried out at one of Senior High School of the tenth grade, as participants, in Sodonghilir. The data were collected from the classroom observation. The result indicated that the total of deixis used in English speaking was 201 data types of deixis from 114 data in utterances. The most type of deixis obtained was person deixis with 183 words in data utterances, the second type was temporal deixis with 11 words in utterances and the least types of deixis was spatial deixis with 7 words in utterances. While the most frequent used of person deixis types during classroom activities were the word